2021
DOI: 10.1101/2021.02.15.431275
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hidden Talents: Poly (I:C)-induced maternal immune activation improves mouse visual discrimination performance and reversal learning in a sex-dependent manner

Abstract: While there is a strong focus on the negative consequences of maternal immune activation (MIA) on the developing brain, very little attention is directed towards potential advantages of early life challenges. In this study we utilized a polyinosine-polycytidylic acid (poly(I:C)) MIA model to test visual discrimination (VD) and reversal learning (RL) in mice using touchscreen technology. Significant sex differences emerged in that MIA improved the latency for males to make a correct choice in the VD task while … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 112 publications
(157 reference statements)
0
8
0
Order By: Relevance
“…However, most of these are sequential in nature, and focus on the effects of a single prenatal exposure followed by a second exposure in adolescence or adulthood. These two-hit models demonstrate that a single prenatal exposure alone may not reveal behavioral deficits or could even be advantageous, while a second exposure later in life can result in impairment ( Giovanoli et al., 2013 , 2016 ; Bilbo et al., 2005 ; Makinson et al., 2019 ; Zhao et al., 2021 ). With the sequential two-hit approach in mice, maternal immune activation acts synergistically with pubertal stress to reveal behavioral impairments and an increase in hippocampal microglia ( Giovanoli et al, 2013 , Giovanoli et al, 2016 ).…”
Section: Translational Value Of Animal Models For Complex Prenatal Exposuresmentioning
confidence: 95%
See 1 more Smart Citation
“…However, most of these are sequential in nature, and focus on the effects of a single prenatal exposure followed by a second exposure in adolescence or adulthood. These two-hit models demonstrate that a single prenatal exposure alone may not reveal behavioral deficits or could even be advantageous, while a second exposure later in life can result in impairment ( Giovanoli et al., 2013 , 2016 ; Bilbo et al., 2005 ; Makinson et al., 2019 ; Zhao et al., 2021 ). With the sequential two-hit approach in mice, maternal immune activation acts synergistically with pubertal stress to reveal behavioral impairments and an increase in hippocampal microglia ( Giovanoli et al, 2013 , Giovanoli et al, 2016 ).…”
Section: Translational Value Of Animal Models For Complex Prenatal Exposuresmentioning
confidence: 95%
“…With the sequential two-hit approach in mice, maternal immune activation acts synergistically with pubertal stress to reveal behavioral impairments and an increase in hippocampal microglia ( Giovanoli et al, 2013 , Giovanoli et al, 2016 ). Additionally, recent evidence shows that maternal immune activation improved performance on a visual discrimination task, although exposed offspring had impaired discrimination and reversal learning if they were challenged with a stressor in adulthood ( Zhao et al., 2021 ). Models less frequently address combined exposures during the prenatal period but the few that do suggest significant interactions.…”
Section: Translational Value Of Animal Models For Complex Prenatal Exposuresmentioning
confidence: 99%
“…One of the most commonly used immunogens in rodent MIA models is polyinosinic:polycytidylic acid (poly(I:C)), a commercially available synthetic analog of double‐stranded RNA that has been shown to induce an extensive collection of innate immune responses (Mueller et al., 2019). These responses lead to a wide array of abnormalities in brain morphology (Li et al., 2009; Meyer et al., 2008), in addition to neurochemical and pharmacological reactions (Zuckerman et al., 2003; Zuckerman & Weiner, 2005) that are associated with altered behaviors and cognitive abilities (Li et al., 2009; Ozawa et al., 2006; Zhao, Mohammed, et al., 2021; Zhao, Tran et al., 2021). Using the poly(I:C) model, one recent study in rats demonstrated that immune challenge at gestational day 12, but not 14, advanced the appearance of vaginal opening in females (Cakan et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most commonly used immunogens in rodent MIA models is polyinosinic:polycytidylic acid (poly (I:C)), a commercially available synthetic analog of double-stranded RNA that has been shown to induce an extensive collection of innate immune responses (Mueller et al, 2019). These responses lead to a wide array of abnormalities in brain morphology (Li et al, 2009;Meyer et al, 2006), in addition to neurochemical, and pharmacological reactions (Zuckerman et al, 2003;Zuckerman and Weiner, 2005) that are associated with altered behaviors and cognitive abilities (Li et al, 2009;Ozawa et al, 2006;Zhao et al, 2021a;Zhao et al, 2021b). Using the poly (I:C) model, one recent study in rats demonstrated that immune challenge at gestational day 12, but not 14, advanced the appearance of vaginal opening in females (Cakan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to an adverse early environment, opportunities for enhanced putatively positive experiences in early life, such as living in an enriched environment (EE) has been shown to confer a number of beneficial effects including enhanced brain plasticity (e.g., increased dendritic branching, synaptogenesis, neurogenesis; (Brenes et al, 2016;Kolb et al, 1998;Van Praag et al, 2000) as well as improvement in cognitive functions (Williams et al, 2001;Zeleznikow-Johnston et al, 2017). Our lab has previously demonstrated that EE rescues disruptions to social motivation, spatial discrimination, and neural markers associated with synaptic plasticity and stress responses following MIA in both mice and rats (Connors et al, 2014;Kentner et al, 2016;Núñez Estevez et al, 2020;Zhao et al, 2021a;Zhao et al, 2020;Zhao et al, 2021b). These findings underscore EE's potential in the mitigation of the behavioral and neurophysiological impairments associated with ELA.…”
Section: Introductionmentioning
confidence: 99%